Improving inferences from coyote (Canis latrans) surveys across Illinois using integrated state-space models - Lauren C. Scopel; Maximilian L. Allen; Thomas J. Benson; Craig A. Miller; Kirk W. Stodola (Mammal Research, 2026)
Anthropogenic influences on landscapes changed wildlife communities immensely over the last century. One notable example of human-derived change is the expansion of coyote ( Canis latrans ) populations following the extirpation of apex carnivores and the inception of industrial agriculture in North America. In Illinois, USA, the Department of Natural Resources estimates relative abundance of coyotes using a variety of survey types, including harvest, participatory science, and observational measures. To examine how different survey methods tracked long-term changes in the state coyote population, we used four datasets of coyote relative abundance in state-space models, deriving estimates of abundance and population growth rates from 1980 to 2023. We compared estimates from individual datasets, as well as estimates from one model that integrated all datasets concurrently. Of the four datasets, only the spotlight survey indicated long-term positive population growth of coyotes, despite the spotlight survey also having the largest observational error. The integrated model showed long-term positive population growth and had high precision compared to the individual models. Individual counties showed high variation, illustrating declines and increases during different decades – fine-scale patterns likely reflect differences in human-caused mortality, prey availability, and habitat quality over time. We support the use of integrated models to combine inferences from relative abundance data, and we encourage the examination of observational biases that may overshadow long-term population changes. Further studies of fine-scale demographic change in coyote populations are needed.

Use of translational fusions to express functional Klebsiella oxytoca dinitrogenase reductase in plant mitochondria - Shoko Okada; Xueqin Wang; Christina M. Gregg; Robert S. Allen; Timothy Rhodes; Vanessa Gillespie; Ingrid Venables; Anu Mathew; Jessica K. Bilyj; Keren Byrne; Robert C. DeFeyter; Trevor D. Rapson; et al. (Plant Molecular Biology, 2026)
Engineering crop plants with the biological nitrogen fixation pathway is a longstanding goal of modern agriculture. Dinitrogenase reductase (NifH) is a critical component of the biological nitrogen fixation pathway, with multiple roles in metal cofactor assembly and catalysis. This enzyme must be folded correctly as a soluble homodimer and loaded with the [4Fe-4S] metallocluster for function. Previous studies have found that Klebsiella oxytoca ( Ko ) and Azotobacter vinelandii ( Av ) NifHs were mostly insoluble when targeted to plant mitochondria. Here we found that a translational fusion of two Ko NifH or Av NifH monomers, forming Ko NifHH or Av NifHH synthetic dimers, produced a soluble protein when targeted to plant mitochondria and co-expressed with the putative peptidyl-prolyl cis–trans isomerase NifM. Ko NifHH isolated after expression in leaf mitochondria at ambient oxygen showed some acetylene reduction activity, which did not require co-expression of the nitrogenase-specific metallocluster machinery NifS and NifU. This activity increased after iron-sulfur cluster reconstitution in vitro with recombinant NifU. In a parallel study, we tested a translational fusion of a variant iron-only dinitrogenase reductase ( Av AnfHv6) monomer that was soluble but not active as-isolated from plant mitochondria ( Av AnfHHv6) (Gregg et al. 2025a). Av AnfHHv6 was abundant and fully soluble when isolated from plant mitochondria, like its monomer. Av AnfHHv6 was not active as-isolated but could be largely activated by iron-sulfur cluster reconstitution in vitro. This study demonstrates how translational fusions help improve solubility and have the potential to generate an active NifH enzyme within plant mitochondria.

Corrigendum to “Tracking the provenance of Greenland-sourced, Holocene aged, individual sand-sized ice-rafted debris using the Pb-isotope compositions of feldspars and 40Ar/39Ar ages of hornblendes” [Earth and Planetary Science Letters 433 (2016) 192–203] - Lee F. White; Ian Bailey; Gavin L. Foster; Georgina Allen; Simon P. Kelley; John T. Andrews; Kelly Hogan; Julian A. Dowdeswell; Craig D. Storey (Earth and Planetary Science Letters, 2026)

Millennial-scale climatic and cultural impacts on vegetation and fire at the southern edge of the Rocky Mountains, USA - Paul D. Henne; Susann Stolze; Natalie M. Kehrwald; Becky Brice; Craig D. Allen (Quaternary Science Reviews, 2026)

Shea-derived cationic surfactants are effective and low-toxicity alternative co-surfactants for foam fractionation of per- and polyfluoroalkyl substances (PFAS) - Craig Klevan; Carolina Gomez Casas; Oren Van Allen; Kelly Mukai; Thatcher LeBlanc; Anita Shukla; Kurt D. Pennell (Journal of Hazardous Materials, 2026)

Effects of Niche Marginality on Hotter‐Drought Tree Mortality in Angiosperms and Gymnosperms - Enric Batllori; William M. Hammond; Alistair Jump; María Ángeles Pérez‐Navarro; Craig D. Allen; Francisco Lloret (Global Ecology and Biogeography, 2025)
Aim Current observations of global tree mortality events associated with drought raise concerns about climate change risks to forests' dynamics and function. It is unclear which forests are more susceptible to pulses of mortality under further changing climates. We examined whether tree mortality related to hotter droughts is predominantly occurring in edge or core populations in niche space and assessed whether mortality patterns are consistent with species' drought tolerances. Location: Global. Time Period: 1970–2020. Major Taxa Studied: Angiosperm and gymnosperm trees. Methods We estimated species' climatic niches on the basis of global occurrences and annual time series of climate. We computed the distance to the niche core of drought mortality sites (982 observations, 44 tree species) and compared it with null models of randomly distributed tree mortality. We assessed how loss of xylem conductance and hydraulic safety margin related to populations' position in niche space and to the degree of climate anomaly during mortality. Results In the year of mortality, 64.3% of the sites were closer to the species' niche edge than the niche core. However, when considering long‐term climate averages, both marginal and central populations experienced drought‐associated pulses of mortality. Overall, tree mortality was related to populations' shifts towards the edge of species' climatic niches and, in angiosperm mortality sites, species' drought tolerances were correlated with the intensity of climatic anomalies. In gymnosperm sites, marginal populations were more affected and other processes, such as heat‐induced stress or cumulative drought effects, may have affected mortality. Main Conclusions Both marginal and central populations, even for highly drought‐tolerant species, are vulnerable to climate change. Climate anomaly magnitude, cumulative drought effects, plant physiological limits and species niche geometry help explain range‐wide patterns of hotter‐drought‐associated tree mortality.

Actor-network analysis of partners facilitating regenerative ranching practices in the US Northern Great Plains - Timothy Pape; Gwendŵr Meredith; David Sandahl; Md Faizul Kabir; Simanti Banerjee; Craig Allen; Elliott Dennis; Mitchell Stephenson (Rangelands, 2025)

Evaluation of co-foaming agents for enhanced removal of per-and polyfluoroalkyl substances (PFAS) by foam fractionation - Craig Klevan; Oren Van Allen; Shana Xia; Kelly Mukai; Andre Gomes; Seth Caines; Matthew J. Woodcock; Kurt D. Pennell (Journal of Hazardous Materials, 2025)

Reconciling scale using the Resist-Accept-Direct (RAD) Framework to improve management of woody encroachment in grasslands - Rheinhardt Scholtz; Daniel R. Uden; Brady W. Allred; Victoria M. Donovan; Jeremy D. Maestas; Scott L. Morford; Matthew O. Jones; David E. Naugle; Samantha M. Cady; Dillon T. Fogarty; Alexander L. Metcalf; Brian Chaffin; et al. (Journal of Environmental Management, 2025)

Pre‐existing phytoplankton biomass concentrations shape coastal plankton response to fire‐generated ash leachate - Nicholas Baetge; Kimberly H. Halsey; Erin J. Hanan; Michael J. Behrenfeld; Allen J. Milligan; Jason R. Graff; Parker Hansen; Craig A. Carlson; Rene M. Boiteau; Eleanor C. Arrington; Jacqueline Comstock; Elisa R. Halewood; et al. (Limnology and Oceanography, 2025)
Climate‐driven warming is projected to intensify wildfires, increasing their frequency and severity globally. Wildfires are an increasingly significant source of atmospheric deposition, delivering nutrients, organic matter, and trace metals to coastal and open ocean waters. These inputs have the potential to fertilize or inhibit microbial growth, yet their ecological impacts remain poorly understood. This study examines how ash leachate, derived from the 2017 Thomas Fire in California and lab‐produced ash from Oregon vegetation, affects coastal plankton communities. Shipboard experiments off the California coast examined how pre‐existing plankton biomass concentrations mediate responses to ash leachates. We found that ash leachate contained dissolved organic matter (DOM) that significantly increased bacterioplankton specific growth rates and DOM remineralization rates but had a negligible effect on bacterioplankton growth efficiency, suggesting low DOM bioavailability. Furthermore, ash‐derived DOM had a higher potential to accumulate in high biomass water, where pre‐existing DOM substrates may better support bacterial metabolism. Ash leachate had a neutral to negative effect on phytoplankton division rates and decreased microzooplankton grazing rates, particularly in low biomass water, leading to increased phytoplankton accumulation. Nanoeukaryotes accumulated in low biomass water, whereas picoeukaryotes and Synechococcus accumulated in high biomass water. Our findings suggest that the influence of ash deposition on DOM cycling, phytoplankton accumulation, and broader marine food web dynamics depends on pre‐existing biomass levels. Understanding these interactions is critical for predicting the biogeochemical consequences of increasing wildfire activity on marine ecosystems.

Addressing key issues and knowledge gaps in resilience science for agriculture - Shana M. Sundstrom; Tala Awada; Elena M. Bennett; Brandon Bestelmeyer; Jennifer Hodbod; Anna Pacheco; Sheri Spiegal; Craig R. Allen (Agricultural Systems, 2025)

Governance of a landscape: The role of formal and informal organizations - Hannah Legatzke; Brian C. Chaffin; Theresa M. Floyd; Simanti Banerjee; Sarah Church; Sabrina Gulab; Samantha Hamlin; Gwendwr R. Meredith; Alexander L. Metcalf; Holly K. Nesbitt; Emily Sutherland-Rowen; Daniel R. Uden; et al. (Journal of Environmental Management, 2025)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Woody plant reinvasion shortens the lifespan of grassland restoration treatments - Dillon T. Fogarty; Michele Beadle; Craig R. Allen; Christine Bielski; Dirac Twidwell (Journal of Environmental Management, 2025)

A Climatological Analysis of Upper‐Level Velocity Potential Using Global Weather Reanalysis, 1959–2020 - Tyler J. Stanfield; Craig Allen Ramseyer (International Journal of Climatology, 2024)
Upper‐level (200 hPa) velocity potential (VP200) is useful in identifying areas of rising or sinking atmospheric motions on varying temporal scales (e.g., weekly, seasonal, interannual) especially in the global tropics. These areas are associated with enhancement (rising motion) or suppression (sinking motion) of tropical convection and subsequent weather phenomena dependent on these processes (e.g., tropical cyclones). This study employed commonly used global weather reanalysis datasets to calculate and compare VP200 on interannual through multidecadal temporal scales and quantify any differences that existed between them from 1959 to 2020 over four key regions of tropical variability (Equatorial Africa, Amazon Basin, Equatorial Central Pacific, and Equatorial Indonesia). To supplement this analysis, the highly correlated variables to VP200 of outgoing longwave radiation (OLR) and daily precipitation rate were used and directly compared with independent OLR and precipitation datasets to determine the reanalysis' level of agreement with the independent data. The ECMWF ERA5 held the highest agreement to these data over all regions examined and was reasoned to have the highest confidence in accurately capturing the variability of VP200 fields for the study period. Confidence was decreased in the usefulness of the NCEP/NCAR Reanalysis 1 as it consistently performed poorly over much of the study domain. The results of this study also emphasised the usefulness in ensemble‐based approaches to assess climate variability and understanding of potential biases and uncertainties that are inherent in these data sources.

Stand structure and disturbance history of old-growth blue pine (Pinus wallichiana) forests in the Bhutan Himalaya - Karma Tenzin; Craig R. Nitschke; Kathryn J. Allen; Benjamin Wagner; Thiet V. Nguyen; Patrick J. Baker (Dendrochronologia, 2024)

Assessment of dietary yeast‐based additives for cultured catfish and tilapia health - Guillaume Cacot; D. Allen Davis; Benjamin R. LaFrentz; Mark R. Liles; Ian A. E. Butts; Craig A. Shoemaker; Benjamin H. Beck; Mark Farmer; Timothy J. Bruce (Journal of Fish Diseases, 2024)
Channel catfish ( Ictalurus punctatus ) and Nile tilapia ( Oreochromis niloticus ) are two aquaculture species of great importance. Intensive production is often hindered by poor growth performance and disease mortality. The aim of this study was to evaluate the potential of a commercial fermented yeast product, DVAQUA, on channel catfish and Nile tilapia growth performance metrics and disease resistance. Channel catfish and Nile tilapia were fed practical diets supplemented with 0%, 0.1% or 0.4% of DVAQUA over approximately 2‐month feeding periods in recirculation aquaculture systems. To assess the potential of the postbiotic against common aquaculture pathogens, juvenile catfish were subsequently challenged by immersion with Edwardsiella ictaluri S97‐773 or virulent Aeromonas hydrophila ML09‐119. Nile tilapia juveniles were challenged by injection with Streptococcus iniae ARS‐98‐60. Serum lysozyme activity, blood chemistry and growth metrics were measured at the end of the feeding period, but no differences were observed across the different metrics, except for survival. For the pathogen challenges, there were no differences in endpoint mortality for channel catfish with either pathogen ( p > .05). In contrast, Nile tilapia survivability to S. iniae infection increased proportionally to the inclusion of DVAQUA ( p = .005). Changes to sera lysozyme activity were also noted in the tilapia trial, with a reduction of activity in the fish fed the 0.4% DVAQUA diet compared to the control diet ( p = .031). Expression profiles of proinflammatory genes and antibodies were also found to be modulated in channel catfish fed the postbiotic, indicating some degree of protective response. These results suggest that this postbiotic may be beneficial in protecting Nile tilapia against S. iniae infection by influencing immune parameters and additional research is needed to evaluate the potential of this DVAQUA for improving catfish health and disease control.

Modeling bark thickness and probability of trunk cavity occurrence relative to tree size in Araucaria angustifolia trees - Vinicius Costa Cysneiros; Marcelo Callegari Scipioni; Craig D. Allen (Trees, 2024)

Correction: Identifying untapped legal capacity to promote multi-level and cross-sectoral coordination of natural resource governance - Nicola Harvey; Ahjond Garmestani; Craig R. Allen; Anoeska Buijze; Marleen van Rijswick (Sustainability Science, 2024)

Identifying untapped legal capacity to promote multi-level and cross-sectoral coordination of natural resource governance - Nicola Harvey; Ahjond Garmestani; Craig R. Allen; Anoeska Buijze; Marleen van Rijswick (Sustainability Science, 2024)
Natural resource governance in the face of climate change represents one of the seminal challenges of the Anthropocene. A number of innovative approaches have been developed in, among others, the fields of ecology, governance, and sustainability sciences for managing uncertainty and scarcity through a coordinated approach to natural resource governance. However, the absence of an enabling legal and regulatory framework has been identified in the literature as one of the primary barriers constraining the formal operationalization of these governance approaches. In this paper, we show how these approaches provide tools for analyzing procedural mandates across governmental levels and sectors in the natural resource governance space. We also find that there has been inadequate consideration of the potential in existing laws and regulations for cross-sectoral and multi-level coordination of natural resource governance. On this basis, we develop and apply a protocol that draws on the traditional legal method of doctrinal analysis to demonstrate how to identify existing, untapped legal capacity to promote coordinated governance of natural resources through an in-depth case study of water resources in South Africa. We then show how these untapped capacities within existing legal structures may be operationalized to improve natural resource governance. Further, this protocol is portable to other countries, provinces (states), and localities around the world.

Communication in the science-policy interface: Evidence from a boundary organization in Nebraska, USA - Sechindra Vallury; Brian C. Chaffin; Samantha L. Hamlin; Craig R. Allen (Environmental Science & Policy, 2023)

Probiotics enhance resistance to Streptococcus iniae in Nile tilapia ( Oreochromis niloticus ) reared in biofloc systems - Uthpala Padeniya; D. Allen Davis; Mark R. Liles; Stacey A. LaFrentz; Benjamin R. LaFrentz; Craig A. Shoemaker; Benjamin H. Beck; Daniel E. Wells; Timothy J. Bruce (Journal of Fish Diseases, 2023)
Biofloc technology is a rearing technique that maintains desired water quality by manipulating carbon and nitrogen and their inherent mixture of organic matter and microbes. Beneficial microorganisms in biofloc systems produce bioactive metabolites that may deter the growth of pathogenic microbes. As little is known about the interaction of biofloc systems and the addition of probiotics, this study focused on this integration to manipulate the microbial community and its interactions within biofloc systems. The present study evaluated two probiotics ( B. velezensis AP193 and BiOWiSH FeedBuilder Syn 3) for use in Nile tilapia ( Oreochromis niloticus ) culture in a biofloc system. Nine independent 3785 L circular tanks were stocked with 120 juveniles (71.4 ± 4.4 g). Tilapia were fed for 16 weeks and randomly assigned three diets: a commercial control diet or a commercial diet top‐coated with either AP193 or BiOWiSH FeedBuilder Syn3. At 14 weeks, the fish were challenged with a low dose of Streptococcus iniae (ARS‐98‐60, 7.2 × 10 7 CFU mL −1 , via intraperitoneal injection) in a common garden experimental design. At 16 weeks, the fish were challenged with a high dose of S. iniae (6.6 × 10 8 CFU mL −1 ) in the same manner. At the end of each challenge trial, cumulative per cent mortality, lysozyme activity and expression of 4 genes ( il‐1β , il6 , il8 and tnfα ) from the spleen were measured. In both challenges, the mortalities of the probiotic‐fed groups were significantly lower ( p S. iniae . Nonetheless, overall il6 expression was lower in fish challenged with a high dose of ARS‐98‐60, while tnfα expression was lower in fish subjected to a lower pathogen dose. Study findings demonstrate the applicability of probiotics as a dietary supplement for tilapia reared in biofloc systems.

Topographic information improves simulated patterns of post‐fire conifer regeneration in the southwest United States - Chang Gyo Jung; Alisa R. Keyser; Cecile C. Remy; Daniel Krofcheck; Craig D. Allen; Matthew D. Hurteau (Global Change Biology, 2023)
The western United States is projected to experience more frequent and severe wildfires in the future due to drier and hotter climate conditions, exacerbating destructive wildfire impacts on forest ecosystems such as tree mortality and unsuccessful post‐fire regeneration. While empirical studies have revealed strong relationships between topographical information and plant regeneration, ecological processes in ecosystem models have either not fully addressed topography‐mediated effects on the probability of plant regeneration, or the probability is only controlled by climate‐related factors, for example, water and light stresses. In this study, we incorporated seedling survival data based on a planting experiment in the footprint of the 2011 Las Conchas Fire into the Photosynthesis and EvapoTranspiration (PnET) extension of the LANDIS‐II model by adding topographic and an additional climatic variable to the probability of regeneration. The modified algorithm included topographic parameters such as heat load index and ground slope and spring precipitation. We ran simulations on the Las Conchas Fire landscape for 2012–2099 using observed and projected climate data (i.e., Representative Concentration Pathway 4.5 and 8.5). Our modification significantly reduced the number of regeneration events of three common southwestern conifer tree species (piñon, ponderosa pine, and Douglas‐fir), leading to decreases in aboveground biomass, regardless of climate scenario. The modified algorithm decreased regeneration at higher elevations and increased regeneration at lower elevations relative to the original algorithm. Regenerations of three species also decreased in eastern aspects. Our findings suggest that ecosystem models may overestimate post‐fire regeneration events in the southwest United States. To better represent regeneration processes following wildfire, ecosystem models need refinement to better account for the range of factors that influence tree seedling establishment. This will improve model utility for projecting the combined effects of climate and wildfire on tree species distributions.

Panarchy theory for convergence - Shana M. Sundstrom; David G. Angeler; Jesse Bell; Michael Hayes; Jennifer Hodbod; Babak Jalalzadeh-Fard; Rezaul Mahmood; Elizabeth VanWormer; Craig R. Allen (Sustainability Science, 2023)

Moreton Bay; A previously unrecognized resting stopover for east-coast of Australia migrating humpback whales - Juliana Castrillon; Raphael Mayaud; Craig Wilson; Greta Dalle Luche; Jenny Allen; Susan Bengtson Nash (Frontiers in Marine Science, 2023)
Humpback whales enter Moreton Bay, in southeast Queensland, Australia, each year during their annual migration. Little is known about the ecological significance of the bay for the humpback whale population. In a region characterised by rapid coastal and maritime development, as well as a growing humpback whale population, there is an urgent need to fill knowledge gaps surrounding the populations’ seasonal distribution and habitat use in these coastal waters. This study procured the first detailed information regarding humpback whale distribution, behaviour, and habitat use within Moreton Bay, relative to the main east coast migratory corridor. It was found that on average 42.41% of the individuals observed on the southern leg of the migration entered the bay. 76.78% of pods entering the bay had accompanying calves and 47.82% of these pods were found to be resting or logging, a behaviour often associated with nursing, at the time of observation. These findings provide strong evidence for a previously undocumented role of Moreton Bay as a resting stopover for migrating humpback whales.

Resilience theory and coerced resilience in agriculture - Shana M. Sundstrom; David G. Angeler; Craig R. Allen (Agricultural Systems, 2023)

The College of American Pathologists Foundation’s See, Test & Treat Program®: an Evaluation of a One-Day Cancer Screening Program Implemented in Mississippi - Michelle S. Williams; Jimmie Wells; Roy J. Duhé; Terrence Shirley; Alexa Lampkin; Maryrose Murphy; Timothy Craig Allen (Journal of Cancer Education, 2022)

Rangelands in a fragmented grass-dominated landscape are vulnerable to tree invasion from roadsides - Katharine F. E. Hogan; Dillon T. Fogarty; Hugh Ellerman; Christopher T. Fill; D. Morales; Baxter Seguin; Daniel R. Uden; Craig R. Allen (Biological Invasions, 2022)
Roadsides can be vectors for tree invasion within rangelands by bisecting landscapes and facilitating propagule spread to interior habitat. Current invasive tree management in North America’s Great Plains focuses on reducing on-site (i.e., interior habitat) vulnerability through on-site prevention and eradication, but invasive tree management of surrounding areas known to serve as invasion vectors, such as roadsides and public rights-of-ways, is sporadic. We surveyed roadsides for invasive tree propagule sources in a central Great Plains grassland landscape to determine how much of the surrounding landscape is potentially vulnerable to roadside invasion, and by which species, and thereby provide insights into the locations and forms of future landcover change. Invasive tree species were widespread in roadsides. Given modest seed dispersal distances of 100–200 m, our results show that roadsides have potential to serve as major sources of rangeland exposure to tree invasion, compromising up to 44% of rangelands in the study area. Under these dispersal distances, funds spent removing trees on rangeland properties may have little impact on the landscape’s overall vulnerability, due to exposure driven by roadside propagule sources. A key implication from this study is that roadsides, while often neglected from management, represent an important component of integrated management strategies for reducing rangeland vulnerability to tree invasion.

Long-term data reveal equivocal evidence for intraguild suppression among sympatric canids - Javan M. Bauder; Maximilian L. Allen; Adam A. Ahlers; Thomas J. Benson; Craig A. Miller; Kirk W. Stodola (Biodiversity and Conservation, 2022)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Nature‐based framework for sustainable afforestation in global drylands under changing climate - Hongyan Liu; Chongyang Xu; Craig D. Allen; Henrik Hartmann; Xiaohua Wei; Dan Yakir; Xiuchen Wu; Pengtao Yu (Global Change Biology, 2022)
Drylands cover more than 40% of Earth's land surface and occur at the margin of forest distributions due to the limited availability of water for tree growth. Recent elevated temperature and low precipitation have driven greater forest declines and pulses of tree mortality on dryland sites compared to humid sites, particularly in temperate Eurasia and North America. Afforestation of dryland areas has been widely implemented and is expected to increase in many drylands globally to enhance carbon sequestration and benefits to the human environment, but the interplay of sometimes conflicting afforestation outcomes has not been formally evaluated yet. Most previous studies point to conflicts between additional forest area and water consumption, in particular water yield and soil conservation/desalinization in drylands, but were generally confined to local and regional scales. Our global synthesis demonstrates that additional tree cover can amplify water consumption through a nonlinear increase in evapotranspiration—depending on tree species, age, and structure—which will be further intensified by future climate change. In this review we identify substantial knowledge gaps in addressing the dryland afforestation dilemma, where there are trade‐offs with planted forests between increased availability of some resources and benefits to human habitats versus the depletion of other resources that are required for sustainable development of drylands. Here we propose a method of addressing comprehensive vegetation carrying capacity, based on regulating the distribution and structure of forest plantations to better deal with these trade‐offs in forest multifunctionality. We also recommend new priority research topics for dryland afforestation, including: responses and feedbacks of dryland forests to climate change; shifts in the ratio of ecosystem ET to tree cover; assessing the role of scale of afforestation in influencing the trade‐offs of dryland afforestation; and comprehensive modeling of the multifunctionality of dryland forests, including both ecophysiological and socioeconomic aspects, under a changing climate.

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

Asymmetry across international borders: Research, fishery and management trends and economic value of the giant sea bass ( Stereolepis gigas ) - Arturo Ramírez‐Valdez; Timothy J. Rowell; Katherine E. Dale; Matthew T. Craig; Larry G. Allen; Juan Carlos Villaseñor‐Derbez; Andrés M. Cisneros‐Montemayor; Arturo Hernández‐Velasco; Jorge Torre; Jennifer Hofmeister; Brad E. Erisman (Fish and Fisheries, 2021)
Co‐operation in the management of shared fish stocks is often necessary to achieve sustainability and reduce uncertainty. The United States of America (USA) and Mexico share a number of fish stocks and marine ecosystems, while there is some binational co‐operation in scientific research, unilateral management decisions are generally the rule. We present a case study using the giant sea bass ( Stereolepis gigas , Polyprionidae) to highlight how these management and research asymmetries can skew national perceptions of population status for a fully transboundary species. Scientific publications and annual funding related to giant sea bass are 7x and 25x higher in the USA, respectively, despite the fact that 73% of the species’ range occurs in Mexico. Conversely, annual fishery production and consumptive value of giant sea bass in Mexico are 19x and 3.5x higher than in the USA, respectively, while the non‐consumptive value related to dive ecotourism is 76x higher in the USA. These asymmetries have generated a distorted view of the population status of the giant sea bass across its entire range. This and other factors related to historical fishery dynamics and policy must be accounted for when assessing population status, and subsequent appropriate management responses, across geopolitical boundaries.

An approach for using multiple indices for monitoring long-term trends of mesopredators at broad spatial scales - Javan M. Bauder; Maximilian L. Allen; Thomas J. Benson; Craig A. Miller; Kirk W. Stodola (Biodiversity and Conservation, 2021)

High Throughput Argon-37 Field System - James C. Hayes; Craig Aalseth; Thomas Alexander; Henning Back; Eric Church; Michael Foxe; Todd Hossbach; Paul Humble; Lance Lidey; Emily Mace; Kerry Meinhardt; Jennifer Mendez; et al. (Pure and Applied Geophysics, 2021)

The conservation status of the world’s freshwater molluscs - Monika Böhm; Nadia I. Dewhurst-Richman; Mary Seddon; Sophie E. H. Ledger; Christian Albrecht; David Allen; Arthur E. Bogan; Jay Cordeiro; Kevin S. Cummings; Annabelle Cuttelod; Gustavo Darrigran; Will Darwall; et al. (Hydrobiologia, 2021)

Marine heatwaves depress metabolic activity and impair cellular acid–base homeostasis in reef‐building corals regardless of bleaching susceptibility - Teegan Innis; Luella Allen‐Waller; Kristen T. Brown; Wesley Sparagon; Christopher Carlson; Elisa Kruse; Ariana S. Huffmyer; Craig E. Nelson; Hollie M. Putnam; Katie L. Barott (Global Change Biology, 2021)
Ocean warming is causing global coral bleaching events to increase in frequency, resulting in widespread coral mortality and disrupting the function of coral reef ecosystems. However, even during mass bleaching events, many corals resist bleaching despite exposure to abnormally high temperatures. While the physiological effects of bleaching have been well documented, the consequences of heat stress for bleaching‐resistant individuals are not well understood. In addition, much remains to be learned about how heat stress affects cellular‐level processes that may be overlooked at the organismal level, yet are crucial for coral performance in the short term and ecological success over the long term. Here we compared the physiological and cellular responses of bleaching‐resistant and bleaching‐susceptible corals throughout the 2019 marine heatwave in Hawai'i, a repeat bleaching event that occurred 4 years after the previous regional event. Relative bleaching susceptibility within species was consistent between the two bleaching events, yet corals of both resistant and susceptible phenotypes exhibited pronounced metabolic depression during the heatwave. At the cellular level, bleaching‐susceptible corals had lower intracellular pH than bleaching‐resistant corals at the peak of bleaching for both symbiont‐hosting and symbiont‐free cells, indicating greater disruption of acid–base homeostasis in bleaching‐susceptible individuals. Notably, cells from both phenotypes were unable to compensate for experimentally induced cellular acidosis, indicating that acid–base regulation was significantly impaired at the cellular level even in bleaching‐resistant corals and in cells containing symbionts. Thermal disturbances may thus have substantial ecological consequences, as even small reallocations in energy budgets to maintain homeostasis during stress can negatively affect fitness. These results suggest concern is warranted for corals coping with ocean acidification alongside ocean warming, as the feedback between temperature stress and acid–base regulation may further exacerbate the physiological effects of climate change.

Simulated Increases in Fire Activity Reinforce Shrub Conversion in a Southwestern US Forest - Alisa R. Keyser; Dan J. Krofcheck; Cécile C. Remy; Craig D. Allen; Matthew D. Hurteau (Ecosystems, 2020)

Bird and invertebrate communities appear unaffected by fracking traffic along rural roads despite dust emissions - Jonathan Spiess; Devan Allen McGranahan; Craig Whippo; Brittany Poling; Aaron L. M. Daigh; Torre Hovick (Ambio, 2020)

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Better Regional Ocean Observing Through Cross-National Cooperation: A Case Study From the Northeast Pacific - John A. Barth; Susan E. Allen; Edward P. Dever; Richard K. Dewey; Wiley Evans; Richard A. Feely; Jennifer L. Fisher; Jonathan P. Fram; Burke Hales; Debby Ianson; Jennifer Jackson; Kim Juniper; et al. (Frontiers in Marine Science, 2019)

To what extent is drought‐induced tree mortality a natural phenomenon? - Roderick J. Fensham; Boris Laffineur; Craig D. Allen (Global Ecology and Biogeography, 2019)
Aim Catastrophic forest mortality due to more extreme rainfall deficits and higher temperatures under future climate scenarios has been predicted. The aim of this study is to explore the magnitude of historical drought‐induced tree mortality under pre‐warming conditions. Location North‐eastern Australia. Time period 1845–2017. Major taxa studied Trees. Methods Field survey, historical analysis and climate analysis. Results We present evidence of 18%–30% tree mortality from recent droughts across three regions of north‐eastern Australia with rainfall deficits less severe than earlier historical droughts. The corrected temperature record represents modest warming at the stations with long records in the vicinity of the study areas. In terms of rainfall deficit the most severe drought on record occurred in the early 20th century, and historical evidence confirms that this drought and earlier droughts before the advent of pastoralism coincided with substantial tree mortality. Main conclusions Dramatic declines in woody biomass in response to drought historically occurred more than once a century and are a natural phenomenon in semi‐arid Australia. The magnitude of drought‐induced tree mortality under natural climate fluctuations requires further investigation in other continents. Widespread drought‐induced tree mortality is not just a recent global change phenomenon and has been underestimated as a natural ecological process. However, even more severe forest die‐off events from more extreme hotter droughts are predicted if Earth’s warming proceeds as currently projected.

Skin sensitization testing needs and data uses by US regulatory and research agencies - Judy Strickland; Amber B. Daniel; David Allen; Cecilia Aguila; Surender Ahir; Simona Bancos; Evisabel Craig; Dori Germolec; Chandramallika Ghosh; Naomi L. Hudson; Abigail Jacobs; David M. Lehmann; et al. (Archives of Toxicology, 2019)

Climate change implications for irrigation and groundwater in the Republican River Basin, USA - Gengxin Ou; Francisco Munoz-Arriola; Daniel R. Uden; Derrel Martin; Craig R. Allen; Nancy Shank (Climatic Change, 2018)

Resilience in Environmental Risk and Impact Assessment: Concepts and Measurement - David G. Angeler; Craig R. Allen; Ahjond Garmestani; Kevin L. Pope; Dirac Twidwell; Mirco Bundschuh (Bulletin of Environmental Contamination and Toxicology, 2018)

The distribution and role of functional abundance in cross‐scale resilience - Shana M. Sundstrom; David G. Angeler; Chris Barichievy; Tarsha Eason; Ahjond Garmestani; Lance Gunderson; Melinda Knutson; Kirsty L. Nash; Trisha Spanbauer; Craig Stow; Craig R. Allen (Ecology, 2018)
The cross‐scale resilience model suggests that system‐level ecological resilience emerges from the distribution of species’ functions within and across the spatial and temporal scales of a system. It has provided a quantitative method for calculating the resilience of a given system and so has been a valuable contribution to a largely qualitative field. As it is currently laid out, the model accounts for the spatial and temporal scales at which environmental resources and species are present and the functional roles species play but does not inform us about how much resource is present or how much function is provided. In short, it does not account for abundance in the distribution of species and their functional roles within and across the scales of a system. We detail the ways in which we would expect species’ abundance to be relevant to the cross‐scale resilience model based on the extensive abundance literature in ecology. We also put forward a series of testable hypotheses that would improve our ability to anticipate and quantify how resilience is generated, and how ecosystems will (or will not) buffer recent rapid global changes. This stream of research may provide an improved foundation for the quantitative evaluation of ecological resilience.

Long-Term Persistence and Fire Resilience of Oak Shrubfields in Dry Conifer Forests of Northern New Mexico - Christopher H. Guiterman; Ellis Q. Margolis; Craig D. Allen; Donald A. Falk; Thomas W. Swetnam (Ecosystems, 2018)

The perpetual state of emergency that sacrifices protected areas in a changing climate - Dirac Twidwell; Carissa L. Wonkka; Christine H. Bielski; Craig R. Allen; David G. Angeler; Jacob Drozda; Ahjond S. Garmestani; Julia Johnson; Larkin A. Powell; Caleb P. Roberts (Conservation Biology, 2018)
A modern challenge for conservation biology is to assess the consequences of policies that adhere to assumptions of stationarity (e.g., historic norms) in an era of global environmental change. Such policies may result in unexpected and surprising levels of mitigation given future climate‐change trajectories, especially as agriculture looks to protected areas to buffer against production losses during periods of environmental extremes. We assessed the potential impact of climate‐change scenarios on the rates at which grasslands enrolled in the Conservation Reserve Program (CRP) are authorized for emergency harvesting (i.e., biomass removal) for agricultural use, which can occur when precipitation for the previous 4 months is below 40% of the normal or historical mean precipitation for that 4‐month period. We developed and analyzed scenarios under the condition that policy will continue to operate under assumptions of stationarity, thereby authorizing emergency biomass harvesting solely as a function of precipitation departure from historic norms. Model projections showed the historical likelihood of authorizing emergency biomass harvesting in any given year in the northern Great Plains was 33.28% based on long‐term weather records. Emergency biomass harvesting became the norm (>50% of years) in the scenario that reflected continued increases in emissions and a decrease in growing‐season precipitation, and areas in the Great Plains with higher historical mean annual rainfall were disproportionately affected and were subject to a greater increase in emergency biomass removal. Emergency biomass harvesting decreased only in the scenario with rapid reductions in emissions. Our scenario‐impact analysis indicated that biomass from lands enrolled in the CRP would be used primarily as a buffer for agriculture in an era of climatic change unless policy guidelines are adapted or climate‐change projections significantly depart from the current consensus.

Structural overshoot of tree growth with climate variability and the global spectrum of drought‐induced forest dieback - Alistair S. Jump; Paloma Ruiz‐Benito; Sarah Greenwood; Craig D. Allen; Thomas Kitzberger; Rod Fensham; Jordi Martínez‐Vilalta; Francisco Lloret (Global Change Biology, 2017)
Ongoing climate change poses significant threats to plant function and distribution. Increased temperatures and altered precipitation regimes amplify drought frequency and intensity, elevating plant stress and mortality. Large‐scale forest mortality events will have far‐reaching impacts on carbon and hydrological cycling, biodiversity, and ecosystem services. However, biogeographical theory and global vegetation models poorly represent recent forest die‐off patterns. Furthermore, as trees are sessile and long‐lived, their responses to climate extremes are substantially dependent on historical factors. We show that periods of favourable climatic and management conditions that facilitate abundant tree growth can lead to structural overshoot of aboveground tree biomass due to a subsequent temporal mismatch between water demand and availability. When environmental favourability declines, increases in water and temperature stress that are protracted, rapid, or both, drive a gradient of tree structural responses that can modify forest self‐thinning relationships. Responses ranging from premature leaf senescence and partial canopy dieback to whole‐tree mortality reduce canopy leaf area during the stress period and for a lagged recovery window thereafter. Such temporal mismatches of water requirements from availability can occur at local to regional scales throughout a species geographical range. As climate change projections predict large future fluctuations in both wet and dry conditions, we expect forests to become increasingly structurally mismatched to water availability and thus overbuilt during more stressful episodes. By accounting for the historical context of biomass development, our approach can explain previously problematic aspects of large‐scale forest mortality, such as why it can occur throughout the range of a species and yet still be locally highly variable, and why some events seem readily attributable to an ongoing drought while others do not. This refined understanding can facilitate better projections of structural overshoot responses, enabling improved prediction of changes in forest distribution and function from regional to global scales.

Tree mortality across biomes is promoted by drought intensity, lower wood density and higher specific leaf area - Sarah Greenwood; Paloma Ruiz‐Benito; Jordi Martínez‐Vilalta; Francisco Lloret; Thomas Kitzberger; Craig D. Allen; Rod Fensham; Daniel C. Laughlin; Jens Kattge; Gerhard Bönisch; Nathan J. B. Kraft; Alistair S. Jump (Ecology Letters, 2017)
Drought events are increasing globally, and reports of consequent forest mortality are widespread. However, due to a lack of a quantitative global synthesis, it is still not clear whether drought‐induced mortality rates differ among global biomes and whether functional traits influence the risk of drought‐induced mortality. To address these uncertainties, we performed a global meta‐analysis of 58 studies of drought‐induced forest mortality. Mortality rates were modelled as a function of drought, temperature, biomes, phylogenetic and functional groups and functional traits. We identified a consistent global‐scale response, where mortality increased with drought severity [log mortality (trees trees −1 year −1 ) increased 0.46 (95% CI = 0.2–0.7) with one SPEI unit drought intensity]. We found no significant differences in the magnitude of the response depending on forest biomes or between angiosperms and gymnosperms or evergreen and deciduous tree species. Functional traits explained some of the variation in drought responses between species (i.e. increased from 30 to 37% when wood density and specific leaf area were included). Tree species with denser wood and lower specific leaf area showed lower mortality responses. Our results illustrate the value of functional traits for understanding patterns of drought‐induced tree mortality and suggest that mortality could become increasingly widespread in the future.

Features of resilience - Elizabeth B. Connelly; Craig R. Allen; Kirk Hatfield; José M. Palma-Oliveira; David D. Woods; Igor Linkov (Environment Systems and Decisions, 2017)

Detecting spatial regimes in ecosystems - Shana M. Sundstrom; Tarsha Eason; R. John Nelson; David G. Angeler; Chris Barichievy; Ahjond S. Garmestani; Nicholas A.J. Graham; Dean Granholm; Lance Gunderson; Melinda Knutson; Kirsty L. Nash; Trisha Spanbauer; et al. (Ecology Letters, 2017)
Research on early warning indicators has generally focused on assessing temporal transitions with limited application of these methods to detecting spatial regimes. Traditional spatial boundary detection procedures that result in ecoregion maps are typically based on ecological potential (i.e. potential vegetation), and often fail to account for ongoing changes due to stressors such as land use change and climate change and their effects on plant and animal communities. We use Fisher information, an information theory‐based method, on both terrestrial and aquatic animal data (U.S. Breeding Bird Survey and marine zooplankton) to identify ecological boundaries, and compare our results to traditional early warning indicators, conventional ecoregion maps and multivariate analyses such as nMDS and cluster analysis. We successfully detected spatial regimes and transitions in both terrestrial and aquatic systems using Fisher information. Furthermore, Fisher information provided explicit spatial information about community change that is absent from other multivariate approaches. Our results suggest that defining spatial regimes based on animal communities may better reflect ecological reality than do traditional ecoregion maps, especially in our current era of rapid and unpredictable ecological change.

Panarchy use in environmental science for risk and resilience planning - David G. Angeler; Craig R. Allen; Ahjond S. Garmestani; Lance H. Gunderson; Igor Linkov (Environment Systems and Decisions, 2016)

The impacts of increasing drought on forest dynamics, structure, and biodiversity in the United States - James S. Clark; Louis Iverson; Christopher W. Woodall; Craig D. Allen; David M. Bell; Don C. Bragg; Anthony W. D'Amato; Frank W. Davis; Michelle H. Hersh; Ines Ibanez; Stephen T. Jackson; Stephen Matthews; et al. (Global Change Biology, 2016)
We synthesize insights from current understanding of drought impacts at stand‐to‐biogeographic scales, including management options, and we identify challenges to be addressed with new research. Large stand‐level shifts underway in western forests already are showing the importance of interactions involving drought, insects, and fire. Diebacks, changes in composition and structure, and shifting range limits are widely observed. In the eastern US , the effects of increasing drought are becoming better understood at the level of individual trees, but this knowledge cannot yet be confidently translated to predictions of changing structure and diversity of forest stands. While eastern forests have not experienced the types of changes seen in western forests in recent decades, they too are vulnerable to drought and could experience significant changes with increased severity, frequency, or duration in drought. Throughout the continental United States, the combination of projected large climate‐induced shifts in suitable habitat from modeling studies and limited potential for the rapid migration of tree populations suggests that changing tree and forest biogeography could substantially lag habitat shifts already underway. Forest management practices can partially ameliorate drought impacts through reductions in stand density, selection of drought‐tolerant species and genotypes, artificial regeneration, and the development of multistructured stands. However, silvicultural treatments also could exacerbate drought impacts unless implemented with careful attention to site and stand characteristics. Gaps in our understanding should motivate new research on the effects of interactions involving climate and other species at the stand scale and how interactions and multiple responses are represented in models. This assessment indicates that, without a stronger empirical basis for drought impacts at the stand scale, more complex models may provide limited guidance.

Quantification of the impacts of finfish aquaculture and bioremediation capacity of integrated multi-trophic aquaculture using a 3D estuary model - Scott Hadley; Karen Wild-Allen; Craig Johnson; Catriona Macleod (Journal of Applied Phycology, 2016)

Developing a genetic baseline for the yellowtail amberjack species complex, Seriola lalandi sensu lato, to assess and preserve variation in wild populations of these globally important aquaculture species - Catherine M. Purcell; Chris L. Chabot; Matthew T. Craig; Natalie Martinez-Takeshita; Larry G. Allen; John R. Hyde (Conservation Genetics, 2015)

Adaptive invasive species distribution models: a framework for modeling incipient invasions - Daniel R. Uden; Craig R. Allen; David G. Angeler; Lucía Corral; Kent A. Fricke (Biological Invasions, 2015)

Emerging Trends in Heart Valve Engineering: Part IV. Computational Modeling and Experimental Studies - Arash Kheradvar; Elliott M. Groves; Ahmad Falahatpisheh; Mohammad K. Mofrad; S. Hamed Alavi; Robert Tranquillo; Lakshmi P. Dasi; Craig A. Simmons; K. Jane Grande-Allen; Craig J. Goergen; Frank Baaijens; Stephen H. Little; et al. (Annals of Biomedical Engineering, 2015)

Spatial Patterns and Functional Redundancies in a Changing Boreal Lake Landscape - David G. Angeler; Craig R. Allen; Daniel R. Uden; Richard K. Johnson (Ecosystems, 2015)

Linking degradation status with ecosystem vulnerability to environmental change - David G. Angeler; Didier L. Baho; Craig R. Allen; Richard K. Johnson (Oecologia, 2015)

Heterogeneity of Mitral Leaflet Matrix Composition and Turnover Correlates with Regional Leaflet Strain - Elizabeth H. Stephens; Patrick S. Connell; Monica M. Fahrenholtz; Tomasz A. Timek; George T. Daughters; Joyce J. Kuo; Aaron M. Patton; Neil B. Ingels; D. Craig Miller; K. Jane Grande-Allen (Cardiovascular Engineering and Technology, 2015)

Cellular and Extracellular Matrix Basis for Heterogeneity in Mitral Annular Contraction - Elizabeth H. Stephens; Monica M. Fahrenholtz; Patrick S. Connell; Tomasz A. Timek; George T. Daughters; Joyce J. Kuo; Aaron M. Patton; Neil B. Ingels; D. Craig Miller; K. Jane Grande-Allen (Cardiovascular Engineering and Technology, 2015)

Modeling macroalgae growth and nutrient dynamics for integrated multi-trophic aquaculture - Scott Hadley; Karen Wild-Allen; Craig Johnson; Catriona Macleod (Journal of Applied Phycology, 2015)

Emerging Trends in Heart Valve Engineering: Part I. Solutions for Future - Arash Kheradvar; Elliott M. Groves; Lakshmi P. Dasi; S. Hamed Alavi; Robert Tranquillo; K. Jane Grande-Allen; Craig A. Simmons; Boyce Griffith; Ahmad Falahatpisheh; Craig J. Goergen; Mohammad R. K. Mofrad; Frank Baaijens; et al. (Annals of Biomedical Engineering, 2015)

Emerging Trends in Heart Valve Engineering: Part II. Novel and Standard Technologies for Aortic Valve Replacement - Arash Kheradvar; Elliott M. Groves; Craig J. Goergen; S. Hamed Alavi; Robert Tranquillo; Craig A. Simmons; Lakshmi P. Dasi; K. Jane Grande-Allen; Mohammad R. K. Mofrad; Ahmad Falahatpisheh; Boyce Griffith; Frank Baaijens; et al. (Annals of Biomedical Engineering, 2015)

Emerging Trends in Heart Valve Engineering: Part III. Novel Technologies for Mitral Valve Repair and Replacement - Arash Kheradvar; Elliott M. Groves; Craig A. Simmons; Boyce Griffith; S. Hamed Alavi; Robert Tranquillo; Lakshmi P. Dasi; Ahmad Falahatpisheh; K. Jane Grande-Allen; Craig J. Goergen; Mohammad R. K. Mofrad; Frank Baaijens; et al. (Annals of Biomedical Engineering, 2015)

Assessing and managing freshwater ecosystems vulnerable to environmental change - David G. Angeler; Craig R. Allen; Hannah E. Birgé; Stina Drakare; Brendan G. McKie; Richard K. Johnson (Ambio, 2014)

Unsupported inferences of high‐severity fire in historical dry forests of the western U nited S tates: response to W illiams and B aker - Peter Z. Fulé; Thomas W. Swetnam; Peter M. Brown; Donald A. Falk; David L. Peterson; Craig D. Allen; Gregory H. Aplet; Mike A. Battaglia; Dan Binkley; Calvin Farris; Robert E. Keane; Ellis Q. Margolis; et al. (Global Ecology and Biogeography, 2014)
Reconstructions of dry western US forests in the late 19th century in A rizona, C olorado and O regon based on G eneral L and O ffice records were used by W illiams & B aker (2012; G lobal E cology and B iogeography , 21 , 1042–1052; hereafter W & B ) to infer past fire regimes with substantial moderate and high‐severity burning. The authors concluded that present‐day large, high‐severity fires are not distinguishable from historical patterns. We present evidence of important errors in their study. First, the use of tree size distributions to reconstruct past fire severity and extent is not supported by empirical age–size relationships nor by studies that directly quantified disturbance history in these forests. Second, the fire severity classification of W & B is qualitatively different from most modern classification schemes, and is based on different types of data, leading to an inappropriate comparison. Third, we note that while W & B asserted ‘surprising’ heterogeneity in their reconstructions of stand density and species composition, their data are not substantially different from many previous studies which reached very different conclusions about subsequent forest and fire behaviour changes. Contrary to the conclusions of W & B , the preponderance of scientific evidence indicates that conservation of dry forest ecosystems in the western U nited S tates and their ecological, social and economic value is not consistent with a present‐day disturbance regime of large, high‐severity fires, especially under changing climate.

Panarchy: Theory and Application - Craig R. Allen; David G. Angeler; Ahjond S. Garmestani; Lance H. Gunderson; C. S. Holling (Ecosystems, 2014)

Discontinuities, cross‐scale patterns, and the organization of ecosystems - Kirsty L. Nash; Craig R. Allen; David G. Angeler; Chris Barichievy; Tarsha Eason; Ahjond S. Garmestani; Nicholas A. J. Graham; Dean Granholm; Melinda Knutson; R. John Nelson; Magnus Nyström; Craig A. Stow; et al. (Ecology, 2014)
Ecological structures and processes occur at specific spatiotemporal scales, and interactions that occur across multiple scales mediate scale‐specific (e.g., individual, community, local, or regional) responses to disturbance. Despite the importance of scale, explicitly incorporating a multi‐scale perspective into research and management actions remains a challenge. The discontinuity hypothesis provides a fertile avenue for addressing this problem by linking measureable proxies to inherent scales of structure within ecosystems. Here we outline the conceptual framework underlying discontinuities and review the evidence supporting the discontinuity hypothesis in ecological systems. Next we explore the utility of this approach for understanding cross‐scale patterns and the organization of ecosystems by describing recent advances for examining nonlinear responses to disturbance and phenomena such as extinctions, invasions, and resilience. To stimulate new research, we present methods for performing discontinuity analysis, detail outstanding knowledge gaps, and discuss potential approaches for addressing these gaps.

The Feasibility of Producing Adequate Feedstock for Year-Round Cellulosic Ethanol Production in an Intensive Agricultural Fuelshed - Daniel R. Uden; Rob B. Mitchell; Craig R. Allen; Qingfeng Guan; Tim D. McCoy (BioEnergy Research, 2013)

Rapid warming accelerates tree growth decline in semi‐arid forests of Inner Asia - Hongyan Liu; A. Park Williams; Craig D. Allen; Dali Guo; Xiuchen Wu; Oleg A. Anenkhonov; Eryuan Liang; Denis V. Sandanov; Yi Yin; Zhaohuan Qi; Natalya K. Badmaeva (Global Change Biology, 2013)
Forests around the world are subject to risk of high rates of tree growth decline and increased tree mortality from combinations of climate warming and drought, notably in semi‐arid settings. Here, we assess how climate warming has affected tree growth in one of the world's most extensive zones of semi‐arid forests, in Inner Asia, a region where lack of data limits our understanding of how climate change may impact forests. We show that pervasive tree growth declines since 1994 in Inner Asia have been confined to semi‐arid forests, where growing season water stress has been rising due to warming‐induced increases in atmospheric moisture demand. A causal link between increasing drought and declining growth at semi‐arid sites is corroborated by correlation analyses comparing annual climate data to records of tree‐ring widths. These ring‐width records tend to be substantially more sensitive to drought variability at semi‐arid sites than at semi‐humid sites. Fire occurrence and insect/pathogen attacks have increased in tandem with the most recent (2007–2009) documented episode of tree mortality. If warming in Inner Asia continues, further increases in forest stress and tree mortality could be expected, potentially driving the eventual regional loss of current semi‐arid forests.

Predictors of regional establishment success and spread of introduced non‐indigenous vertebrates - Craig R. Allen; Kristine T. Nemec; Donald A. Wardwell; Justin D. Hoffman; Mathew Brust; Karie L. Decker; Daniel Fogell; Jennifer Hogue; Aaron Lotz; Thaddeus Miller; Marcy Pummill; Luis E. Ramirez‐Yañez; et al. (Global Ecology and Biogeography, 2013)
Aim To provide the first analysis of predictors of both establishment and spread, both within and across taxa, for all vertebrate taxa within a region. We used F lorida, USA , as our study system because it has a well‐documented history of introduction and invasion, and is a hotspot for biological invasions. Location F lorida, USA. Methods We analysed non‐indigenous species ( NIS ) data from peninsular F lorida – which included both successful and unsuccessful introductions from all vertebrate classes – to determine the best predictors of both establishment and spread for fish (65 species), herpetofauna (63 species), birds (71 species) and mammals (25 species). We used 10 variables proposed to be associated with the establishment and spread of NIS : body mass, geographic origin, reproductive rate, diet generalism, native‐range size, latitude of native range, number of NIS present at date of introduction, presence of NIS congeners, morphological proximity to other NIS (in terms of body mass) and propagule pressure. A multimodel selection process was used with an information‐theoretic approach to determine the best fit models for predicting establishment and spread of NIS . We selected a priori plausible predictive models for establishment and spread. Results Large native‐range size and small body mass best predicted establishment of non‐indigenous herpetofauna. The presence of NIS congeners had the largest positive effect on the establishment of non‐indigenous fish. For mammals, the number of NIS present at the time of introduction best explained establishment. No single model best explained bird establishment. For all taxa but birds, the number of NIS present at time of introduction was included in at least one of the best‐supported models for explaining spread. Main conclusions Our analyses suggest that predictors of establishment and spread differ across vertebrate taxa at the scale studied. Most predictive variables can be interpreted as measures of competitive interactions among species.

Effect of food restriction on cocaine locomotor sensitization in Sprague–Dawley rats - Craig P. Allen; Yan Zhou; Francesco Leri (Psychopharmacology, 2013)

An assessment of air pollution and its attributable mortality in Ulaanbaatar, Mongolia - Ryan W. Allen; Enkhjargal Gombojav; Baldorj Barkhasragchaa; Tsogtbaatar Byambaa; Oyuntogos Lkhasuren; Ofer Amram; Tim K. Takaro; Craig R. Janes (Air Quality, Atmosphere & Health, 2013)

The effects of acute and chronic steady state methadone on memory retrieval in rats - Erin Cummins; Craig P. Allen; Alexander Ricchetti; Emily Boughner; Kayla Christenson; Megan Haines; Cheryl L. Limebeer; Linda A. Parker; Francesco Leri (Psychopharmacology, 2012)

Species, Functional Groups, and Thresholds in Ecological Resilience - SHANA M. SUNDSTROM; CRAIG R. ALLEN; CHRIS BARICHIEVY (Conservation Biology, 2012)
The cross‐scale resilience model states that ecological resilience is generated in part from the distribution of functions within and across scales in a system. Resilience is a measure of a system's ability to remain organized around a particular set of mutually reinforcing processes and structures, known as a regime. We define scale as the geographic extent over which a process operates and the frequency with which a process occurs. Species can be categorized into functional groups that are a link between ecosystem processes and structures and ecological resilience. We applied the cross‐scale resilience model to avian species in a grassland ecosystem. A species’ morphology is shaped in part by its interaction with ecological structure and pattern, so animal body mass reflects the spatial and temporal distribution of resources. We used the log‐transformed rank‐ordered body masses of breeding birds associated with grasslands to identify aggregations and discontinuities in the distribution of those body masses. We assessed cross‐scale resilience on the basis of 3 metrics: overall number of functional groups, number of functional groups within an aggregation, and the redundancy of functional groups across aggregations. We assessed how the loss of threatened species would affect cross‐scale resilience by removing threatened species from the data set and recalculating values of the 3 metrics. We also determined whether more function was retained than expected after the loss of threatened species by comparing observed loss with simulated random loss in a Monte Carlo process. The observed distribution of function compared with the random simulated loss of function indicated that more functionality in the observed data set was retained than expected. On the basis of our results, we believe an ecosystem with a full complement of species can sustain considerable species losses without affecting the distribution of functions within and across aggregations, although ecological resilience is reduced. We propose that the mechanisms responsible for shaping discontinuous distributions of body mass and the nonrandom distribution of functions may also shape species losses such that local extinctions will be nonrandom with respect to the retention and distribution of functions and that the distribution of function within and across aggregations will be conserved despite extinctions.

A unique genome-wide association analysis in extended Utah high-risk pedigrees identifies a novel melanoma risk variant on chromosome arm 10q - Craig Teerlink; James Farnham; Kristina Allen-Brady; Nicola J. Camp; Alun Thomas; Sancy Leachman; Lisa Cannon-Albright (Human Genetics, 2012)

Effects of biotic disturbances on forest carbon cycling in the U nited S tates and C anada - Jeffrey A. Hicke; Craig D. Allen; Ankur R. Desai; Michael C. Dietze; Ronald J. Hall; Edward H. (Ted) Hogg; Daniel M. Kashian; David Moore; Kenneth F. Raffa; Rona N. Sturrock; James Vogelmann (Global Change Biology, 2012)
Forest insects and pathogens are major disturbance agents that have affected millions of hectares in N orth A merica in recent decades, implying significant impacts to the carbon ( C ) cycle. Here, we review and synthesize published studies of the effects of biotic disturbances on forest C cycling in the U nited S tates and C anada. Primary productivity in stands was reduced, sometimes considerably, immediately following insect or pathogen attack. After repeated growth reductions caused by some insects or pathogens or a single infestation by some bark beetle species, tree mortality occurred, altering productivity and decomposition. In the years following disturbance, primary productivity in some cases increased rapidly as a result of enhanced growth by surviving vegetation, and in other cases increased slowly because of lower forest regrowth. In the decades following tree mortality, decomposition increased as a result of the large amount of dead organic matter. Net ecosystem productivity decreased immediately following attack, with some studies reporting a switch to a C source to the atmosphere, and increased afterward as the forest regrew and dead organic matter decomposed. Large variability in C cycle responses arose from several factors, including type of insect or pathogen, time since disturbance, number of trees affected, and capacity of remaining vegetation to increase growth rates following outbreak. We identified significant knowledge gaps, including limited understanding of carbon cycle impacts among different biotic disturbance types (particularly pathogens), their impacts at landscape and regional scales, and limited capacity to predict disturbance events and their consequences for carbon cycling. We conclude that biotic disturbances can have major impacts on forest C stocks and fluxes and can be large enough to affect regional C cycling. However, additional research is needed to reduce the uncertainties associated with quantifying biotic disturbance effects on the N orth A merican C budget.

Global Competency and Issues in Contemporary Education / Agroforestry - Susan Moore; Erin Sills; Lee Allen; Douglas Frederick; Frederick Cubbage; John Garland; Julie Lydick; Gordon Holley; Jodi Roberts; Stephen Grado; Zhu Ning; Shannon Fowler; et al. (Journal of Forestry, 2011)
34We performed a five year integrated research, extension and education project aimed at strengthening global competence of students and faculty through collaboration in forestry. We sought to improve our students' ability to cooperate, increase their understanding of global dynamics of forestry markets and enhance their knowledge of various approaches to forest management and conservation with Chile as the focus. The project had four key components: (1) facilitate faculty and student involvement in Chile through Spanish language training, a website, and visits by Chilean faculty; (2) support NC State faculty and student research and study in Chile through travel grants and study tours; (3) build on faculty sabbaticals in Chile by funding student research assistants; and (4) disseminate information from Chile through multiple channels to both the university and professional communities. The faculty exchange visits; graduate student research; and participation of NCSU students, faculty and staff in the study tours to Chile had substantial effects when the participants returned to the US and disseminated information about their experiences through both formal and informal mechanisms. Both students and faculty at NCSU are more aware of forestry research, policy and management in Chile. Faculty at NCSU and Chilean universities Universidad de Concepción and Universidad de Austral have established a strong basis for collaboration and are continuing to work together on funding proposals, research, and papers. Students who participated in the study tours learned about both the culture and forestry in Chile, including similarities, differences, and lessons for the US. This presentation will describe the activities, outcomes and ongoing impacts of the project.

Millennial precipitation reconstruction for the Jemez Mountains, New Mexico, reveals changingb drought signal - Ramzi Touchan; Connie A. Woodhouse; David M. Meko; Craig Allen (International Journal of Climatology, 2011)
Drought is a recurring phenomenon in the American Southwest. Since the frequency and severity of hydrologic droughts and other hydroclimatic events are of critical importance to the ecology and rapidly growing human population of this region, knowledge of long‐term natural hydroclimatic variability is valuable for resource managers and policy‐makers. An October–June precipitation reconstruction for the period AD 824–2007 was developed from multi‐century tree‐ring records of Pseudotsuga menziesii (Douglas‐fir), Pinus strobiformis (Southwestern white pine) and Pinus ponderosa (Ponderosa pine) for the Jemez Mountains in Northern New Mexico. Calibration and verification statistics for the period 1896–2007 show a high level of skill, and account for a significant portion of the observed variance (>50%) irrespective of which period is used to develop or verify the regression model. Split‐sample validation supports our use of a reconstruction model based on the full period of reliable observational data (1896–2007). A recent segment of the reconstruction (2000–2006) emerges as the driest 7‐year period sensed by the trees in the entire record. That this period was only moderately dry in precipitation anomaly likely indicates accentuated stress from other factors, such as warmer temperatures. Correlation field maps of actual and reconstructed October–June total precipitation, sea surface temperatures and 500‐mb geopotential heights show characteristics that are similar to those indicative of El Niño–Southern Oscillation patterns, particularly with regard to ocean and atmospheric conditions in the equatorial and north Pacific. Our 1184‐year reconstruction of hydroclimatic variability provides long‐term perspective on current and 20th century wet and dry events in Northern New Mexico, is useful to guide expectations of future variability, aids sustainable water management, provides scenarios for drought planning and as inputs for hydrologic models under a broader range of conditions than those provided by historical climate records. Copyright © 2010 Royal Meteorological Society

Age estimation and lead–radium dating of Antarctic toothfish (Dissostichus mawsoni) in the Ross Sea - Cassandra M. Brooks; Allen H. Andrews; Julian R. Ashford; Nakul Ramanna; Christopher D. Jones; Craig C. Lundstrom; Gregor M. Cailliet (Polar Biology, 2011)

A 15 000‐year record of climate change in northern New Mexico, USA, inferred from isotopic and elemental contents of bog sediments - Luz M. Cisneros‐Dozal; Jeffrey M. Heikoop; Julianna Fessenden; R. Scott Anderson; Philip A. Meyers; Craig D. Allen; Marcey Hess; Toti Larson; George Perkins; Michael Rearick (Journal of Quaternary Science, 2010)
Elemental (C, N, Pb) and isotopic ( δ 13 C, δ 15 N) measurements of cored sediment from a small bog in northern New Mexico reveal changes in climate during the Late Pleistocene and Holocene. Abrupt increases in Pb concentration and δ 13 C values ca. 14 420 cal. YBP indicate significant runoff to the shallow lake that existed at that time. Weathering and transport of local volcanic rocks resulted in the delivery of Pb‐bearing minerals to the basin, while a 13 C‐enriched terrestrial vegetation source increased the δ 13 C values of the sedimentary material. Wet conditions developed over a 300 a period and lasted for a few hundred years. The Younger Dryas period (ca. 12 700–11 500 cal. YBP) caused a reduction in terrestrial productivity reflected in decreasing C/N values, δ 15 N values consistently greater than 0‰ and low organic content. By contrast, aquatic productivity increased during the second half of this period, evidenced by increasing δ 13 C values at the time of highest abundance of algae. Dry conditions ca. 8 000–6 000 cal. YBP were characterised by low organic carbon content and high Pb concentrations, the latter suggesting enhanced erosion and aeolian transport of volcanic rock. The range in δ 13 C, δ 15 N and C/N values in the sedimentary record fall within the range of modern plants, except during the periods of runoff and drought. The sedimentary record provides evidence of natural climate variability in northern New Mexico, including short‐ (multi‐centennial) and long‐(millennial) term episodes during the Late Pleistocene and Holocene. Copyright © 2010 John Wiley & Sons, Ltd.

Analyzing complex traits with congenic strains - Haifeng Shao; David S. Sinasac; Lindsay C. Burrage; Craig A. Hodges; Pamela J. Supelak; Mark R. Palmert; Carol Moreno; Allen W. Cowley; Howard J. Jacob; Joseph H. Nadeau (Mammalian Genome, 2010)

Growth, carbon‐isotope discrimination, and drought‐associated mortality across a Pinus ponderosa elevational transect - NATE G. McDOWELL; CRAIG D. ALLEN; LAURA MARSHALL (Global Change Biology, 2010)
Drought‐ and insect‐associated tree mortality at low‐elevation ecotones is a widespread phenomenon but the underlying mechanisms are uncertain. Enhanced growth sensitivity to climate is widely observed among trees that die, indicating that a predisposing physiological mechanism(s) underlies tree mortality. We tested three, linked hypotheses regarding mortality using a ponderosa pine ( Pinus ponderosa ) elevation transect that experienced low‐elevation mortality following prolonged drought. The hypotheses were: (1) mortality was associated with greater growth sensitivity to climate, (2) mortality was associated with greater sensitivity of gas exchange to climate, and (3) growth and gas exchange were correlated. Support for all three hypotheses would indicate that mortality results at least in part from gas exchange constraints. We assessed growth using basal area increment normalized by tree basal area [basal area increment (BAI)/basal area (BA)] to account for differences in tree size. Whole‐crown gas exchange was indexed via estimates of the CO 2 partial pressure difference between leaf and atmosphere ( p a − p c ) derived from tree ring carbon isotope ratios ( δ 13 C), corrected for temporal trends in atmospheric CO 2 and δ 13 C and elevation trends in pressure. Trees that survived the drought exhibited strong correlations among and between BAI, BAI/BA, p a − p c , and climate. In contrast, trees that died exhibited greater growth sensitivity to climate than trees that survived, no sensitivity of p a − p c to climate, and a steep relationship between p a − p c and BAI/BA. The p a − p c results are consistent with predictions from a theoretical hydraulic model, suggesting trees that died had a limited buffer between mean water availability during their lifespan and water availability during drought – i.e., chronic water stress. It appears that chronic water stress predisposed low‐elevation trees to mortality during drought via constrained gas exchange. Continued intensification of drought in mid‐latitude regions may drive increased mortality and ecotone shifts in temperate forests and woodlands.

Options for National Parks and Reserves for Adapting to Climate Change - Jill S. Baron; Lance Gunderson; Craig D. Allen; Erica Fleishman; Donald McKenzie; Laura A. Meyerson; Jill Oropeza; Nate Stephenson (Environmental Management, 2009)

Rapid shoot regeneration in industrial ‘high starch’ sweetpotato (Ipomoea batatas L.) genotypes - Monica Santa-Maria; Kenneth V. Pecota; Craig G. Yencho; George Allen; Bryon Sosinski (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Interactions Across Spatial Scales among Forest Dieback, Fire, and Erosion in Northern New Mexico Landscapes - Craig D. Allen (Ecosystems, 2007)

Challenges in the application of geometric constraint models - Craig R. McClain; Ethan P. White; Allen H. Hurlbert (Global Ecology and Biogeography, 2007)
Discerning the processes influencing geographical patterns of species richness remains one of the central goals of modern ecology. Traditional approaches to exploring these patterns have focused on environmental and ecological correlates of observed species richness. Recently, some have suggested these approaches suffer from the lack of an appropriate null model that accounts for species ranges being constrained to occur within a bounded domain. Proponents of these null geometric constraint models (GCMs), and the mid‐domain effect these models produce, argue their utility in identifying meaningful gradients in species richness. This idea has generated substantial debate. Here we discuss what we believe are the three major challenges in the application of GCMs. First, we argue that there are actually two equally valid null models for the random placement of species ranges within a domain, one of which actually predicts a uniform distribution of species richness. Second, we highlight the numerous decisions that must be made to implement a GCM that lead to marked differences in the predictions of the null model. Finally, we discuss challenges in evaluating the importance of GCMs once they have been implemented.

Multimodel Inference and the Understanding of Complexity, Discontinuity, and Normadism - Craig R. Allen; Denis A. Saunders (Ecosystems, 2006)

Predictors of Introduction Success in the South Florida Avifauna - Craig R. Allen (Biological Invasions, 2006)

A 21st Century Perspective on Postfire Seeding - Jon E. Keeley; Craig D. Allen; Julio Betancourt; Geneva W. Chong; C.J. Fotheringham; Hugh D. Safford (Journal of Forestry, 2006)

When Landscaping Goes Bad: The Incipient Invasion of Mahonia bealei in the Southeastern United States - Craig R. Allen; Ahjond S. Garmestani; Jill A. LaBram; Amanda E. Peck; Luanna B. Prevost (Biological Invasions, 2006)

The Use of Discontinuities and Functional Groups to Assess Relative Resilience in Complex Systems - Craig R. Allen; L. Gunderson; A. R. Johnson (Ecosystems, 2005)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

A Landscape Perspective for Forest Restoration - Thomas D. Sisk; Melissa Savage; Donald A. Falk; Craig D. Allen; Esteban Muldavin; Patrick McCarthy (Journal of Forestry, 2005)

Nitrogen mineralization in a pecan (Carya illinoensis K. Koch)?cotton (Gossypium hirsutum L.) alley cropping system in the southern United States - Samuel C. Allen; Shibu Jose; P. K. R. Nair; Barry J. Brecke; Vimala D. Nair; Donald A. Graetz; Craig L. Ramsey (Biology and Fertility of Soils, 2005)

Histone deacetylase inhibitors induce reactivation of herpes simplex virus type 1 in a latency-associated transcript–independent manner in neuronal cells - Robert J Danaher; Robert J Jacob; Marion R Steiner; Will R Allen; James M Hill; Craig S Miller (Journal of NeuroVirology, 2005)

Competition for 15N-labeled fertilizer in a pecan (Carya illinoensis K. Koch)-cotton (Gossypium hirsutum L.) alley cropping system in the southern United States - Samuel C. Allen; Shibu Jose; P.K.R. Nair; Barry J. Brecke; Craig L. Ramsey (Plant and Soil, 2004)

Baclofen does not alter the reinforcing, subject-rated or cardiovascular effects of intranasal cocaine in humans - Joshua A. Lile; William W. Stoops; Timothy S. Allen; Paul E. A. Glaser; Lon R. Hays; Craig R. Rush (Psychopharmacology, 2004)

The importance of rapid, disturbance‐induced losses in carbon management and sequestration - David D. Breshears; Craig D. Allen (Global Ecology and Biogeography, 2002)
Management of terrestrial carbon fluxes is being proposed as a means of increasing the amount of carbon sequestered in the terrestrial biosphere. This approach is generally viewed only as an interim strategy for the coming decades while other longer‐term strategies are developed and implemented — the most important being the direct reduction of carbon emissions. We are concerned that the potential for rapid, disturbance‐induced losses may be much greater than is currently appreciated, especially by the decision‐making community. Here we wish to: (1) highlight the complex and threshold‐like nature of disturbances — such as fire and drought, as well as the erosion associated with each — that could lead to carbon losses; (2) note the global extent of ecosystems that are at risk of such disturbance‐induced carbon losses; and (3) call for increased consideration of and research on the mechanisms by which large, rapid disturbance‐induced losses of terrestrial carbon could occur . Our lack of ability as a scientific community to predict such ecosystem dynamics is precluding the effective consideration of these processes into strategies and policies related to carbon management and sequestration. Consequently, scientists need to do more to improve quantification of these potential losses and to integrate them into sound, sustainable policy options.

Body Mass Patterns Predict Invasions and Extinctions in Transforming Landscapes - Craig R. Allen; Elizabeth A. Forys; C. S. Holling (Ecosystems, 1999)

Original Articles: Ecological Resilience, Biodiversity, and Scale - Garry Peterson; Craig R. Allen; C. S. Holling (Ecosystems, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)